Legalization of Nikah Sirri: A Solution to Obtain Marital Status Recognition Among Diverse Cultural Groups in Indonesia - Darmawan, Aldy; Sulfinadia, Hamda; Efrinaldi, Efrinaldi; Elfia, Elfia; Izzati, Nurul (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
This article examines the background behind couples from various ethnic groups in Indonesia opting for unregistered marriages and their efforts to obtain legal recognition of their marital status from the state. The research aims to understand the motivations of couples from different cultural backgrounds when deciding to marry in secrecy and how they then seek to legalize their unions through court decisions on marital status confirmation. The method used in this study is field research with a descriptive qualitative approach. Primary data was obtained through in-depth interviews with 14 interethnic couples such as Minang, Batak and Javanese in Padang City who filed petitions for marital status confirmation to the local Class 1A Religious Court. The findings reveal that preferences over unregistered marriages are influenced by the social, cultural and religious backgrounds of each ethnic group. This condition necessitates contextual adjustments in providing legal solutions to the issue of unregistered marriages so that they can be accepted by all parties from the existing cultural diversity. In conclusion, marital status confirmation in Religious Courts can be an effective legal solution for interethnic couples with unregistered marriages in Indonesia to obtain formal recognition of their marital status. However, a profound understanding of the prevailing socio-cultural values in each community is needed so that decisions on marital status confirmation do not contradict and can be well accepted by all parties.